Bicycle and Pedestrian Counts at Signalized Intersections Using Existing Infrastructure: Opportunities and Challenges. Issue 1 (2017) - Kothuri, Sirisha; Nordback, Krista; Schrope, Andrew; Phillips, Taylor; Figliozzi, Miguel
Bicycling and walking have gained increased attention recently; however, systematic bicycle and pedestrian counts are still scarce. At intersections, transportation agencies are interested in counting bicycles and pedestrians and leveraging for counting purposes, if possible, existing signal detection equipment. This study evaluated four counting technologies: inductive loops and a thermal camera to count bicycles and passive infrared counters and pedestrian signal actuation data to count pedestrians. The four technologies were tested in a parking lot (controlled environment) and in an intersection (real-world environment). The findings revealed that while the inductive loops and thermal camera counted bicycles accurately in a controlled environment, the loops and cameras failed to do so at an intersection. Passive infrared counters were found to count pedestrians accurately at the intersection sidewalk, and pedestrian signal actuation data could be a cost-effective surrogate for pedestrian demand at signalized intersections.